Preparation method of airfield pavement thin layer repairing material
By using components such as high-belitt sulfaluminate cement, ceramic powder and resin microcapsules wrapped in the thin-layer repair material of the airport road surface, combined with specific preparation steps and the method of adjusting the shear force to release the ring monomer, the problem of repairing the surface surface peeling and fine cracks is solved, and the repair effect is achieved with high efficiency, heat resistance and crack resistance, and has self-repairing function.
Patent Information
- Application Number
- CN202510156326.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively repair surface peeling caused by durability damage and fine cracks caused by freeze-thaw cycles.
Using a preparation method of thin-layer repair material on the airport road surface, the resin microcapsules are used to prepare the repair material through specific stirring and distillation steps, and the resin microcapsules are used to crush and release the ring monomer by adjusting the shear force to achieve the self-repair function.
This method can effectively reduce the dimensional change rate of repair materials, enhance the heat resistance and crack resistance of repair materials, achieve high adhesion and waterproofness, and is suitable for repairing thin layers of airport road surfaces, and has self-repairing functions.
Smart Images

Figure CN119822765A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a repair material, and in particular to a method for preparing a thin-layer repair material for an airport pavement. Background Art
[0002] Most of the runways at my country's airports are made of cement concrete, also known as rigid pavements. Under the long-term effects of aircraft loads and the environment, the pavements often suffer from varying degrees of damage. In order to improve the performance of the runway and extend its life, preventive maintenance measures need to be taken to maintain the runway pavement in a timely manner. Corresponding maintenance measures need to be taken for different types of damage. When structural damage occurs (such as pavement fracture), the bad blocks need to be cut off for repair.
[0003] However, the problem with the above method is that when the durability damage pavement surface peels off, if the bad block repair method is still used, it will cause structural damage to the pavement panel, thereby affecting the safety of runway operation. There is currently no effective solution to repair or eliminate the fine cracks caused by freeze-thaw cycles.
[0004] In view of this, there is a need in the art to develop a method for preparing a thin layer of airport pavement repair material. Summary of the invention
[0005] The main purpose of the present disclosure is to provide a method for preparing a thin layer of airport pavement repair material, so as to effectively solve the problems raised by the inventor in the above background technology.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a thin-layer repair material for an airport pavement, wherein the repair material comprises high-belite sulphoaluminate cement, ceramic micropowder, cyclic monomer, powder defoamer, silicone hydrophobic agent, acrylic redispersible latex powder, low-viscosity HPMC, fine aggregate, polycarboxylic acid high-efficiency water reducing agent, catalyst, retarder, heat-resistant fiber and polymer fiber; The cyclic monomer is encapsulated in a resin microcapsule, and the cyclic monomer is prepared by adding a liquid cyclic monomer to a solution containing an isocyanate and an anionic emulsifier, and then adding diamine dropwise after ultrasonic emulsification to form the cyclic monomer encapsulated in the resin microcapsule; the catalyst is encapsulated in a gelatin capsule, and the catalyst is encapsulated into a hollow gelatin capsule by a conventional method to form a catalyst encapsulated in a gelatin capsule; The glass transition temperature of the acrylic redispersible latex powder is 2-6°C; the catalyst is a Grubbs catalyst; the retarder is any two of tartaric acid, sodium citrate and sucrose; the heat-resistant fiber is one or more of glass fiber, carbon fiber, ceramic fiber and basalt fiber; The composition of the repair material is, by mass fraction, 30-45% of high-belite sulphoaluminate cement, 5-25% of cyclic monomers wrapped in resin microcapsules, 10-30% of ceramic micropowder, 0.1-0.5% of powder defoamer, 0.1-0.5% of silicone hydrophobic agent, 5-15% of acrylic redispersible latex powder, 0.01-0.1% of low-viscosity HPMC, 10-30% of fine aggregate, 0.1-0.5% of polycarboxylic acid high-efficiency water reducing agent, 0.05-0.2% of catalyst, 0.05-0.3% of retarder, 0.05-0.2% of heat-resistant fiber and 0.05-0.2% of polymer fiber.
[0007] Preferably, the particle size range of the cyclic monomer encapsulated by the resin microcapsule is 0.0375-0.10 mm, the particle size range of the ceramic micropowder is 0.0375-0.125 mm, and the particle size range of the acrylic redispersible latex powder is 0.0375-0.25 mm.
[0008] Preferably, the diamine includes one or more of ethylenediamine, propylenediamine and meta-phenylenediamine, and the resin microcapsule is a polyurea microcapsule.
[0009] Preferably, the cyclic monomer encapsulated by the resin microcapsule is a cyclopentadiene monomer or a norbornene monomer.
[0010] Preferably, the fine aggregate includes any one of silica sand particles, ceramic sand and ceramsite.
[0011] Preferably, the polymer fiber includes one or more of polyester fiber, polypropylene staple fiber, polyacrylonitrile fiber and polyvinyl alcohol fiber.
[0012] Preferably, the high-belite sulphoaluminate cement is used as the main cementitious material, and its shrinkage rate is about one-tenth of that of ordinary Portland cement. It has high early strength, and the compressive strength can be increased by more than 85% in 7 days. It can reduce the dimensional change rate of the rapid repair material, match the concrete with the lesions, bear the load together, and reduce cracking.
[0013] Preferably, the acrylic redispersible latex powder is used as an organic gelling material to form a rigid-flexible complement with cement, and can also greatly improve the adhesion, so that the repair material has a certain flexibility to reduce cracking caused by external forces. After the slurry of the repair material hardens, a unified network structure is formed inside, which improves the density and resists the invasion of external water. The acrylic redispersible latex powder molecules have a large number of hydrophobic groups that can improve the anti-seepage performance and make it waterproof.
[0014] A method for preparing a thin layer of airport pavement repair material comprises the following steps: Step 1: prepare the various components of the repair material, and add the required mass proportion of high-belite sulphoaluminate cement, ceramic powder, cyclic monomer wrapped in resin microcapsule, fine aggregate, heat-resistant fiber, polymer fiber, low-viscosity HPMC and acrylic redispersible latex powder into a stirring tank, and stir at room temperature for ten minutes; Step 2: Add powder defoamer, silicone water repellent, polycarboxylic acid high-efficiency water reducer and catalyst into a stirring kettle at 80°C, mix and stir for ten minutes, let stand for eight hours and cool to room temperature; Step 3, distilling the mixture obtained in step 2 under reduced pressure, and washing the distillate at room temperature; Step 4: Transfer the distillate in step 3 to a vacuum kettle, prepare a retarder solution, mix the retarder and water to form a retarder solution, and then add the retarder solution into the vacuum kettle to mix it with the distillate to complete the preparation of the repair material.
[0015] In view of this, compared with the prior art, the beneficial effects of the present invention are: (I) In the present application, high-belite sulphoaluminate cement is selected with a low dimensional change rate, so that it can match the concrete with lesions, bear the load together and reduce cracking. The retarder can extend the initial setting time of the quick-repair material to ensure the construction operation time of the material and speed up the completion of the repair and commissioning. The heat-resistant fiber and polymer fiber composite improve the tensile bonding strength between the components, reduce the deformation caused by internal stress caused by early dimensional deformation, and can enhance the heat resistance and crack resistance of the repair material.
[0016] (ii) In this application, the adhesion to the substrate is high, there is no hollowing after repair, it is cold-proof and frost-resistant, the water absorption rate of the material is extremely low, it can withstand low-temperature freeze-thaw cycles below -40°C, it is fast to use, and it only needs to be maintained for 2 hours after construction before it can be used. It is suitable for the repair of thin layers of airport pavements.
[0017] (III) In the present application, the cyclic monomer is wrapped with resin microcapsules to form a physical isolation between the cyclic monomer and the catalyst. The shear force applied to the repair material can be adjusted to break at least a portion of the resin microcapsules to release the cyclic monomer. The cyclic monomer penetrates out of the microcapsules and contacts the catalyst to rapidly solidify. When the repair material is being constructed, the shear force applied to the repair material can be adjusted to prevent at least a portion of the resin microcapsules from breaking and lurking in the airport pavement after repair, thereby releasing the cyclic monomer when the airport pavement is damaged again to achieve the self-repairing function. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a flow chart of the method for preparing the thin layer repair material for airport pavement provided by the present invention; DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] See also Figure 1 , the present invention provides the following embodiments: A method for preparing a thin-layer repair material for an airport pavement, wherein the repair material comprises high-belite sulphoaluminate cement, ceramic micropowder, cyclic monomer, powder defoamer, silicone hydrophobic agent, acrylic redispersible latex powder, low-viscosity HPMC, fine aggregate, polycarboxylic acid high-efficiency water reducing agent, catalyst, retarder, heat-resistant fiber and polymer fiber; The cyclic monomer is encapsulated in a resin microcapsule, and the cyclic monomer is prepared by adding a liquid cyclic monomer to a solution containing an isocyanate and an anionic emulsifier, and then adding diamine dropwise after ultrasonic emulsification to form a cyclic monomer encapsulated in the resin microcapsule; the catalyst is encapsulated in a gelatin capsule, and the catalyst is encapsulated into a hollow gelatin capsule by a conventional method to form a catalyst encapsulated in a gelatin capsule; The glass transition temperature of acrylic redispersible latex powder is 2-6°C; the catalyst is Grubbs catalyst; the retarder is any two of tartaric acid, sodium citrate and sucrose; the heat-resistant fiber is one or more of glass fiber, carbon fiber, ceramic fiber and basalt fiber; The composition of the repair material is calculated by mass fraction as follows: 30-45% of high belite sulphoaluminate cement, 5-25% of cyclic monomers encapsulated in resin microcapsules, 10-30% of ceramic micropowder, 0.1-0.5% of powder defoamer, 0.1-0.5% of silicone hydrophobic agent, 5-15% of acrylic redispersible latex powder, 0.01-0.1% of low viscosity HPMC, 10-30% of fine aggregate, 0.1-0.5% of polycarboxylic acid high-efficiency water reducing agent, 0.05-0.2% of catalyst, 0.05-0.3% of retarder, 0.05-0.2% of heat-resistant fiber and 0.05-0.2% of polymer fiber.
[0021] Specifically, the particle size range of the cyclic monomer encapsulated by the resin microcapsule is 0.0375-0.10 mm, the particle size range of the ceramic micropowder is 0.0375-0.125 mm, and the particle size range of the acrylic redispersible latex powder is 0.0375-0.25 mm.
[0022] Specifically, the diamine includes one or more of ethylenediamine, propylenediamine and metaphenylenediamine, and the resin microcapsule is a polyurea microcapsule.
[0023] Specifically, the cyclic monomer encapsulated by the resin microcapsule is a cyclopentadiene monomer or a norbornene monomer.
[0024] Specifically, the fine aggregate includes any one of silica sand particles, pottery sand and ceramsite.
[0025] Specifically, the polymer fiber includes one or more of polyester fiber, polypropylene staple fiber, polyacrylonitrile fiber and polyvinyl alcohol fiber.
[0026] Specifically, high-belite sulphoaluminate cement, as the main cementitious material, has a shrinkage rate of about one-tenth of that of ordinary Portland cement. It has high early strength and its compressive strength can be increased by more than 85% in 7 days. It can reduce the dimensional change rate of rapid repair materials, match with diseased concrete, jointly bear the load, and reduce cracking.
[0027] Specifically, acrylic redispersible latex powder, as an organic gelling material, forms a rigid-flexible complement with cement, and can also greatly improve the adhesion, so that the repair material has a certain flexibility to reduce cracking caused by external forces. After the slurry of the repair material hardens, a unified network structure is formed inside, which improves the density and resists the invasion of external water. In addition, the acrylic redispersible latex powder molecules have a large number of hydrophobic groups that can improve the anti-seepage performance and make it waterproof.
[0028] A method for preparing a thin layer of airport pavement repair material comprises the following steps: Step 1: Prepare the various components of the repair material, and add the required mass proportion of high-belite sulphoaluminate cement, ceramic powder, cyclic monomer wrapped in resin microcapsule, fine aggregate, heat-resistant fiber, polymer fiber, low-viscosity HPMC and acrylic redispersible latex powder into a stirring tank, and stir at room temperature for ten minutes; Step 2: Add powder defoamer, silicone water repellent, polycarboxylic acid high-efficiency water reducer and catalyst into a stirring kettle at 80°C, mix and stir for ten minutes, let stand for eight hours and cool to room temperature; Step 3, distilling the mixture obtained in step 2 under reduced pressure, and washing the distillate at room temperature; Step 4: Transfer the distillate in step 3 to a vacuum kettle, prepare a retarder solution, mix the retarder and water to form a retarder solution, and then add the retarder solution into the vacuum kettle to mix it with the distillate to complete the preparation of the repair material.
[0029] The specific implementation of this embodiment is as follows: by wrapping the cyclic monomer with resin microcapsules, a physical isolation is formed between the cyclic monomer and the catalyst, and the shear force applied to the repair material can be adjusted so that at least a part of the resin microcapsules are broken to release the cyclic monomer, and the cyclic monomer penetrates out of the microcapsules and contacts the catalyst and then solidifies rapidly. When the repair material is being constructed, the shear force applied to the repair material can be adjusted so that at least a part of the resin microcapsules are not broken and lurk in the airport pavement after repair, so that the cyclic monomer is released when the airport pavement is damaged again, so as to achieve the function of self-repair; high belite sulphoaluminate cement with a size change rate is selected Low, so that it can match the diseased concrete, bear the load together, reduce cracking, retarder can prolong the initial setting time of the quick repair material to ensure the construction operation time of the material and speed up the completion of the repair and put it into use. The heat-resistant fiber and polymer fiber composite improve the tensile bonding strength between the components, reduce the deformation caused by internal stress caused by early dimensional deformation, and can enhance the heat resistance and crack resistance of the repair material; it has high adhesion to the substrate, no hollowing after repair, cold and frost resistance, the material has extremely low water absorption, can withstand low-temperature cycles below -40°C, freeze-thaw, fast use speed, only needs 2 hours of maintenance after construction before it can be passed, and is suitable for the repair of thin layers of airport pavements.
[0030] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0031] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A thin layer repair material for airport pavement, characterized by: The composite components of the repair material include high-belite sulphoaluminate cement, ceramic micropowder, cyclic monomer, powder defoamer, silicone hydrophobic agent, acrylic redispersible latex powder, low-viscosity HPMC, fine aggregate, polycarboxylic acid high-efficiency water reducing agent, catalyst, retarder, heat-resistant fiber and polymer fiber; The cyclic monomer is encapsulated in a resin microcapsule, and the cyclic monomer is prepared by adding a liquid cyclic monomer to a solution containing an isocyanate and an anionic emulsifier, and then adding diamine dropwise after ultrasonic emulsification to form the cyclic monomer encapsulated in the resin microcapsule; the catalyst is encapsulated in a gelatin capsule, and the catalyst is encapsulated into a hollow gelatin capsule by a conventional method to form a catalyst encapsulated in a gelatin capsule; The glass transition temperature of the acrylic redispersible latex powder is 2-6°C; the catalyst is a Grubbs catalyst; the retarder is any two of tartaric acid, sodium citrate and sucrose; the heat-resistant fiber is one or more of glass fiber, carbon fiber, ceramic fiber and basalt fiber; The composition of the repair material is, by mass fraction, 30-45% of high-belite sulphoaluminate cement, 5-25% of cyclic monomers wrapped in resin microcapsules, 10-30% of ceramic micropowder, 0.1-0.5% of powder defoamer, 0.1-0.5% of silicone hydrophobic agent, 5-15% of acrylic redispersible latex powder, 0.01-0.1% of low-viscosity HPMC, 10-30% of fine aggregate, 0.1-0.5% of polycarboxylic acid high-efficiency water reducing agent, 0.05-0.2% of catalyst, 0.05-0.3% of retarder, 0.05-0.2% of heat-resistant fiber and 0.05-0.2% of polymer fiber.
2. The airport pavement thin layer repair material according to claim 1, characterized in that: The usable particle size range of the cyclic monomer encapsulated by the resin microcapsule is 0.0375-0.10 mm, the usable particle size range of the ceramic micropowder is 0.0375-0.125 mm, and the usable particle size range of the acrylic redispersible latex powder is 0.0375-0.25 mm.
3. The airport pavement thin layer repair material according to claim 1, characterized in that: The diamine includes one or more of ethylenediamine, propylenediamine and metaphenylenediamine, and the resin microcapsule is a polyurea microcapsule.
4. The airport pavement thin layer repair material according to claim 1, characterized in that: The cyclic monomer encapsulated by the resin microcapsule is a cyclopentadiene monomer or a norbornene monomer.
5. The airport pavement thin layer repair material according to claim 1, characterized in that: The fine aggregate includes any one of silica sand particles, pottery sand and ceramsite.
6. The airport pavement thin layer repair material according to claim 1, characterized in that: The polymer fiber includes one or more of polyester fiber, polypropylene staple fiber, polyacrylonitrile fiber and polyvinyl alcohol fiber.
7. The airport pavement thin layer repair material according to claim 1, characterized in that: The high-belite sulphoaluminate cement is used as the main cementitious material, and its shrinkage rate is about one-tenth of that of ordinary Portland cement. It has high early strength and its compressive strength can be increased by more than 85% in 7 days. It can reduce the dimensional change rate of rapid repair materials, match with the diseased concrete, bear the load together, and reduce cracking.
8. The airport pavement thin layer repair material according to claim 1, characterized in that: The acrylic redispersible latex powder, as an organic gelling material, forms a rigid-flexible complement with cement, and can also greatly improve the adhesion, so that the repair material has a certain flexibility to reduce cracking caused by external forces. After the slurry of the repair material hardens, a unified network structure is formed inside, which improves the density and resists the invasion of external water. The acrylic redispersible latex powder molecules have a large number of hydrophobic groups that can improve the anti-seepage performance and make it waterproof.
9. A method for preparing a thin layer of airport pavement repair material according to claims 1-8, characterized in that: The following steps are involved: Step 1: prepare the various components of the repair material, and add the required mass proportion of high-belite sulphoaluminate cement, ceramic powder, cyclic monomer wrapped in resin microcapsule, fine aggregate, heat-resistant fiber, polymer fiber, low-viscosity HPMC and acrylic redispersible latex powder into a stirring tank, and stir at room temperature for ten minutes; Step 2: Add powder defoamer, silicone water repellent, polycarboxylic acid high-efficiency water reducer and catalyst into a stirring kettle at 80°C, mix and stir for ten minutes, let stand for eight hours and cool to room temperature; Step 3, distilling the mixture obtained in step 2 under reduced pressure, and washing the distillate at room temperature; Step 4: Transfer the distillate in step 3 to a vacuum kettle, prepare a retarder solution, mix the retarder and water to form a retarder solution, and then add the retarder solution into the vacuum kettle to mix it with the distillate to complete the preparation of the repair material.
Citation Information
Patent Citations
Airfield pavement repairing material self-compacting at room temperature and preparation method thereof
CN107298543A
Room temperature self-curing airport pavement repairing material and preparation method thereof
CN107382138A
Rapid repairing material for airport parking apron and preparation method thereof
CN110937870A